Application of E-Litigation in Unlawful Acts at the Sidoarjo District Court - Nurfatin Yollandita Mandovi (Yustisia Tirtayasa: Jurnal Tugas Akhir, 2022)
Along with the times, it is not surprising that at this time the development of information technology is very influential on the ease in all human activities, everything can be solved very quickly and simply through this information technology. Not only affecting the social aspect, information technology is also a legal aspect and brings changes in the law enforcement process from conventional to digital/electronic. Digitization can be found in litigation. E-Litigation is an electronic trial that includes the process of sending answers, both replicas, duplicates, conclusions to judge decisions. E-Litigation is part of the e-court or electronic judiciary which is a form of implementation of the use of information technology from the Supreme Court of the Republic of Indonesia which is carried out to help facilitate tasks within the judiciary by realizing a simple trial, short process, and low cost. small. This is of course as stated in the legal basis for E-Litigation Regulation Number 1 of 2019 concerning Procedures for Electronic Cases and Trials in Courts, which is confirmed by Supreme Court Decision Number 129/KMA/SK/VIII/2019. E-Litigation is a service from e-court that applies within the scope of the District Court, Religious Court, and State Administrative Court with the types of cases namely Civil, Religious Civil Cases, State Administrative Cases, Military Cases. From the District Courts in Indonesia, the District Courts that have implemented the E-Litigation system are the Sidoarjo District Courts, especially in cases of Unlawful Acts. which can have an impact on the realization of a more modern, technology-based, effective and efficient judicial system.